Zu welchen Themen suchen Angehörige von Demenzbetroffenen telefonische oder emailbasierte Beratung auf? Aktuelle Ergebnisse des bundesweiten Beratungsangebots der Deutschen Alzheimer Gesellschaft e.V. - Pendergrass, Anna; Weiß, Saskia; Grässel, Elmar (Gesundheitswesen, 2019)
BACKGROUND: Since 15 years, the Alzheimer 's Telephone of the German Alzheimer Society (Deutsche Alzheimer Gesellschaft e.V.; DAlzG), a nationwide psychosocial counseling service, has been offering support for people with dementia (PwD) and their families. The aim of this study was to evaluate: a) why informal PwD caregivers seek telephone counseling, b) whether these telephone calls are one-time counseling or long-term support, and c) whether the telephone inquiries differ from the email-based inquiries with regard to the addressed issues. MATERIALS AND METHODS: The data are based on the inquiries of 3,744 informal caregivers, which consulted the DAlzG in 2015. Sociodemographic data on the informal caregivers and the PwD, the characteristics of the telephone call, and the topics addressed in the email inquiries were collected. RESULTS: 70.3% of the callers were female. Most of them (59.9%) were the children (in-law) of and half of them (49.7%) lived with PwD. More than two-thirds of the callers (70%) were seeking help in dealing with the person with dementia (e. g. challenging behavior) and 36.5% of the relatives needed recommendations for further local help and assistance. In the third place, the calls were related to financial and legal topics (23.5%). 92.2% of the calls were one-time consultations. The addressed issues in the email inquiries did not significantly differ from the topics discussed over the telephone. DISCUSSION: On many topics there is a need for further "on site" consultation. Doctors and other health professionals should therefore be actively involved in counseling relatives of PwD.
CRIS-Team Scopus Importer:2019-12-20